2017
DOI: 10.1002/art.40189
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster and Tofacitinib: Clinical Outcomes and the Risk of Concomitant Therapy

Abstract: ObjectivePatients with rheumatoid arthritis (RA) are at increased risk of herpes zoster (HZ), and the risk appears to be increased in patients treated with tofacitinib. The aim of this study was to evaluate whether concomitant treatment with conventional synthetic disease‐modifying antirheumatic drugs (csDMARDs) or glucocorticoids (GCs) contributes to the increased risk of HZ in RA patients treated with tofacitinib.MethodsHZ cases were identified from the databases of 2 phase I, 9 phase II, 6 phase III, and 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
157
3
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(183 citation statements)
references
References 50 publications
14
157
3
9
Order By: Relevance
“…One infectious complication that is more common in tofacitinib and baricitinib treated patients than patients treated with biologics is reactivation of varicella zoster virus (VZV; herpes zoster) . RA itself represents an independent risk factor for reactivation of VZV, followed by age and the use of prednisone, and the risk of herpes zoster infections in patients treated with tofacitinib is further increased by concomitant use of steroids and methotrexate .…”
Section: Side Effects Of First Generation Jakinibsmentioning
confidence: 99%
“…One infectious complication that is more common in tofacitinib and baricitinib treated patients than patients treated with biologics is reactivation of varicella zoster virus (VZV; herpes zoster) . RA itself represents an independent risk factor for reactivation of VZV, followed by age and the use of prednisone, and the risk of herpes zoster infections in patients treated with tofacitinib is further increased by concomitant use of steroids and methotrexate .…”
Section: Side Effects Of First Generation Jakinibsmentioning
confidence: 99%
“…Además se señalaba que la edad mayor de 65 años, el uso de glucocorticoides y la dosis de tofacitinib fueron factores de riesgo independientes para la aparición de HZ. [3] En relación con la protección que conferiría la vacunación específica contra el virus de la varicela zoster (VVZ), un ensayo clínico en fase II controlado con placebo que incluyó a 112 pacientes mayores de 50 años con AR activa y que recibían metotrexato de terapia de base, se administró la vacunación a todos los casos incluidos, aleatorizándose un grupo que recibió tofacitinib y otro placebo; llegándose a determinar a las 6 semanas los niveles de IgG específicos de VVZ, sin encontrar diferencias estadísticamente significativas de los niveles de anticuerpos entre ambos grupos y manteniendo respuestas inmunomediadas humorales y celulares similares. [4] …”
Section: Tofacitinib Y Riesgo De Reactivación De Herpes Zósterunclassified
“…Tofacitinib is an oral Janus kinase inhibitor for the treatment of RA. Tofacitinib has been reported to increase HZ risk in patients with RA, and the risk is higher still in older patients, those receiving corticosteroids , and in certain Asian populations, particularly Japanese and Korean patients . In an analysis of data from phase II, phase III, and long‐term extension (LTE) studies in patients with RA who received tofacitinib 5 or 10 mg twice daily (BID) without prior LZV (per protocol, some patients may have received LZV), the HZ incidence rate (IR) was 4.4 per 100 patient‐years (95% confidence interval [95% CI] 3.8–4.9) globally and 9.2 per 100 patient‐years (95% CI 7.5–11.4) in Japan/Korea .…”
Section: Introductionmentioning
confidence: 99%
“…In an analysis of data from phase II, phase III, and long‐term extension (LTE) studies in patients with RA who received tofacitinib 5 or 10 mg twice daily (BID) without prior LZV (per protocol, some patients may have received LZV), the HZ incidence rate (IR) was 4.4 per 100 patient‐years (95% confidence interval [95% CI] 3.8–4.9) globally and 9.2 per 100 patient‐years (95% CI 7.5–11.4) in Japan/Korea . Analysis of phase I, phase II, phase III, and LTE study data showed that most HZ events in tofacitinib‐treated patients with RA were not serious (per the investigator's assessment) and resolved with standard antiviral treatment . Increased HZ risk versus placebo has also been observed with another Janus kinase inhibitor, baricitinib, in an analysis of data pooled from phase I, phase II, phase III, and LTE studies.…”
Section: Introductionmentioning
confidence: 99%